Evaluating Online Environments for Elementary Teachers’ Literacy-Oriented Professional Learning - Minuk, Alexandra; Pamela Beach; Favret, Elena (Alberta Journal of Educational Research, 2023)
As elementary teachers increasingly turn to online environments for their literacy-oriented professional learning, evaluating website quality is of growing importance. Using screen capture recordings of participants’ navigations, the purpose of this study was to identify the types of online learning environments that elementary teachers use to enhance their literacy practice as well as to evaluate website quality. Findings reveal that teachers access ten main types of online environments. Those that were resource-based were accessed with the highest frequency despite having the lowest quality. Implications for the design of online learning environments as well as self-directed learning are explored in depth. Keywords: teacher professional development; teacher professional learning; self-directed learning; website evaluation; literacy Comme les enseignants du primaire se tournent de plus en plus vers les environnements en ligne pour leur apprentissage professionnel axé sur la littératie, l'évaluation de la qualité des sites Web revêt une importance croissante. Reposant sur des enregistrements de captures d'écran de la navigation des participants, l'objectif de cette étude était d'identifier les types d'environnements d'apprentissage en ligne que les enseignants du primaire utilisent pour améliorer leur pratique de l'alphabétisation ainsi que d'évaluer la qualité des sites Web. Les résultats révèlent que les enseignants accèdent à dix types principaux d'environnements en ligne. Ceux qui sont basés sur les ressources sont les plus utilisés, même si leur qualité est la plus faible. Les implications pour la conception d'environnements d'apprentissage en ligne ainsi que pour l'apprentissage autodirigé sont explorées en profondeur. Mots clés : développement professionnel des enseignants ; apprentissage professionnel des enseignants ; apprentissage autodirigé ; évaluation des sites Web ; alphabétisation.